Effects of Sodium Azide on Platelet Function - Stibbe, Jeanne; Holmsen, Holm (Thrombosis and Haemostasis, 1977)
Sodium azide in low concentrations (0.1-10 μM) was found to have inhibitory effects on human platelet function. Primary aggregation induced by ADP, epinephrine, thrombin and the ionophore A 23187 was decreased. To evaluate the effect of azide apart from secondary processes, the platelets were treated with indomethacin to prevent prostaglandin/thromboxane synthesis for all inducers; in addition, effects of secreted ADP, in the case of thrombin and A 23187, was prevented by the presence of creatine phosphate plus creatine phosphokinase. ADP, epinephrine and A 23187, but not thrombin-induced primary aggregates, dispersed immediately upon addition of azide. Azide powerfully inhibited dense granule secretion induced by collagen, ADP and epinephrine as measured both by 14C-serotonin secretion and as judged by secondary aggregation. Shape change induced by ADP, thrombin or A 23187 was not affected. Azide had no effect on energy metabolism. Since the aggregation experiments were performed in the presence of indomethacin, and malondialdehyde formation from arachidonic acid was not affected by azide, it seemed unlikely that the inhibition by azide of platelet function was related to inhibition of synthesis of prostaglandins and thromboxanes. It is concluded that azide exerts its effects directly on the common pathway for platelet responses.Abbreviations used: AA: arachidonic acid; PG-TX: PGG2, PGH2 and thromboxane A2; ETYA: 5, 8, 11, 14-eicosa-tetraynoic acid; MDA: malondialdehyde; PGE1 prostaglandin E1; db-c-GMP: dibutyryl 3’, 5’-cyclic guanosine monophosphate; ADP: adenosine diphosphate; c-AMP: 3’, 5’-cyclic adenosine monophosphate; CP: creatine phosphate; CPK: creatine phosphokinase; PRP: píatelet-rich plasma; PPP: platelet-poor plasma; GFP: gel filtered platelets.